PARTISIPASI AKTIF MASYARAKAT DALAM MENGOPTIMALKAN APLIKASI SMART CITY UNTUK KOTA BANDUNG YANG LEBIH CERDAS DAN TERINTEGRASI - Muhammad Alfian Zuhri; Aji Rahmatullah; Muhammad Ghifari Arfananda; Ivan Darmawan (Triwikrama: Jurnal Ilmu Sosial, 2024)
This study examines the active role of citizens in optimizing smart city applications in Bandung to improve public service efficiency and data integration. Findings reveal that citizen participation significantly influences the successful implementation of smart city applications. Enhancing digital literacy and public understanding of technology is essential for system sustainability. With adequate infrastructure support and stakeholder collaboration, these applications can create a smarter and more integrated city. This research provides strategic insights to strengthen the role of citizens in the smart city ecosystem.